2015
DOI: 10.1016/j.resuscitation.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Managing cardiac arrest with refractory ventricular fibrillation in the emergency department: Conventional cardiopulmonary resuscitation versus extracorporeal cardiopulmonary resuscitation

Abstract: The management of refractory ventricular fibrillation in the emergency department remains challenging, as evidenced by an overall survival rate of 35% in this study. Patients with refractory ventricular fibrillation receiving E-CPR had a trend toward higher survival rates and significantly improved neurological outcomes than those receiving C-CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 32 publications
2
95
0
3
Order By: Relevance
“…Only ECLS if CPR >10 min or repetitive arrest events without ROSC >20 min. No ECLS if unwitnessed OHCA or no bystander CPRConventional CPR8187459646965674143 (21–60)30 (15–48)Maekawa et al [15]Witnessed OHCA of presumed cardiac origin, CPR >20 minInitiation of ECPR was dependent on the attending physiciansConventional CPR5310954718373406 b 49 (41–59)56 (47–66)2 (0–8)5 (0–9)Sakamoto et al [16]OHCA based on VF/VT, no ROSC >15 min after hospital arrival, <45 min between emergency call and hospital arrival; cardiac originAssignment of facility to ECPR or CPR groupConventional CPR2601945658908964593811 b Shin et al [17]IHCA, witnessed, CPR >10 minAccording to the discretion of the CPR team leaderConventional CPR85321606262634526417 a 42 ± 2641 ± 37– d – d Siao et al [18]Cardiac arrest with initial VF (start CPR <5 min), no ROSC after 10 min CPR…”
Section: Resultsmentioning
confidence: 99%
“…Only ECLS if CPR >10 min or repetitive arrest events without ROSC >20 min. No ECLS if unwitnessed OHCA or no bystander CPRConventional CPR8187459646965674143 (21–60)30 (15–48)Maekawa et al [15]Witnessed OHCA of presumed cardiac origin, CPR >20 minInitiation of ECPR was dependent on the attending physiciansConventional CPR5310954718373406 b 49 (41–59)56 (47–66)2 (0–8)5 (0–9)Sakamoto et al [16]OHCA based on VF/VT, no ROSC >15 min after hospital arrival, <45 min between emergency call and hospital arrival; cardiac originAssignment of facility to ECPR or CPR groupConventional CPR2601945658908964593811 b Shin et al [17]IHCA, witnessed, CPR >10 minAccording to the discretion of the CPR team leaderConventional CPR85321606262634526417 a 42 ± 2641 ± 37– d – d Siao et al [18]Cardiac arrest with initial VF (start CPR <5 min), no ROSC after 10 min CPR…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9] While no prospective randomized studies have been completed examining the outcomes of ECPRtreated patients in comparison to conventional resuscitation, ECPR for OHCA is typically initiated between 45 and 75 minutes after the initial cardiac arrest, 6,7 an elapsed duration of resuscitation at which survival with conventional resuscitation appears to be rare. 17 The Alfred Hospital and Victorian EMS system in Melbourne, Australia, which provides similar hospital and pre-hospital services to those in our region, recently described the results of an ECPR protocol, demonstrating 56% neurologically intact survival in a carefully selected group of patients with refractory OHCA treated with ECPR.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Survival rates have been reported up to approximately 50%. [5][6][7][8][9] Although ECPR may increase the proportion of survivors in selected OHCA patients, it is a resourceintensive therapy, requiring the attendance of a specially trained team that may include physicians, surgeons, cardiac perfusionists, and skilled nursing staff, as well as specialized protocols, equipment, and hospital resources. The aims of this descriptive study were: (1) to identify patients within our region who fulfilled a hypothetical set of ECPR criteria and estimate the number who would have been candidates for ECPR therapy; and (2) to determine the baseline outcomes of ECPR-eligible patients treated with conventional resuscitation to estimate the potential gains of an ECPR program.…”
Section: Introductionmentioning
confidence: 99%
“…Siao et al suggested that VF is refractory if no return of spontaneous circulation is achieved after more than 10 min of conventional ACLS effort. 29 However, in their series this definition translated into a mean duration of resuscitation effort before ECMO was begun of 69.9±49.6 min. They also suggested that at least 3 shocks be delivered in patients with shockable rhythms before such are considered refractory.…”
Section: Safety Of the Ems Crewmentioning
confidence: 99%